Efektifitas Latihan Basic Life Support (BLS) Pada Masyarakat Awam (Forum Anak Provinsi Jambi) Untuk Penanganan Korban Kecelakaan Lalulintas Di Kota Jambi - Andi Subandi; Try Wahyu Purnomo; Sri Mustika Aulia (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to determine the increase in knowledge and skills of children forum participants in receiving Basic Life Support (BLS) training as evidenced in simulations outside the hospital. Researchers used a quantitative approach with a quasi-experimental method. This study uses pre and post design stages in assessing the effectiveness of training for emergency handling of traffic accidents. From the results of the Basic Life Support (BLS) study showed a significant increase as seen from the increase in the average pre-test (41.82) and post-test (73.45) scores. the difference was significant in the group of participants (p value <0.05). The material in the Basic Life Support (BLS) training that was delivered was the handling of emergency conditions for traffic accident victims, socialization of legal rules and procedures regarding the evacuation and transportation of patients from the crime scene to health facilities.